1990
DOI: 10.1073/pnas.87.9.3599
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies from a patient with scleroderma CREST recognized kinetochores of the higher plant Haemanthus.

Abstract: Human autoantibodies from a patient with scleroderma CREST (calcinosis, Raynaud phenomenon, esophageal dismotility, scierodactyly, telangiectasia) were used to immunostain kinetochores on chromosomes in endosperm of the seed of the monocot Haemanthus katherinae Bak. Kinetochores of mitotic chromosomes and prekinetochores of interphase cells were specifically stained using conventional indirect immunofluorescence procedures as well as a nonfading immunogold-silver-enhanced technique and analyzed by fluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Identification of titin as a chromosomal component Human autoimmune sera have been used successfully to identify a wide range of nuclear antigens, including both single-and double-stranded DNA, RNA, histones, small nuclear RNA-binding proteins, transcription factors, nuclear larnins, topo I and II, heterochromatin-associated proteins and centromere proteins (Tan, 1982;Earnshaw and Rothfield, 1985;Tan et al, 1987;Tan, 1989;Mole-Bajer et al, 1990;Earnshaw and Rattner, 1991;Tan, 1991;Fritzler, 1997;Saunders et al, 1993;Shibata et al, 1993;Bejarano and Valdivia, 1996;Spain et al, 1997;Sugiura et al, 1997). We recently identified titin as a chromosomal component using a human autoimmune scleroderma serum (Machado, 1998;Machado et al, 1998).…”
Section: Machado and Andrewmentioning
confidence: 99%
“…Identification of titin as a chromosomal component Human autoimmune sera have been used successfully to identify a wide range of nuclear antigens, including both single-and double-stranded DNA, RNA, histones, small nuclear RNA-binding proteins, transcription factors, nuclear larnins, topo I and II, heterochromatin-associated proteins and centromere proteins (Tan, 1982;Earnshaw and Rothfield, 1985;Tan et al, 1987;Tan, 1989;Mole-Bajer et al, 1990;Earnshaw and Rattner, 1991;Tan, 1991;Fritzler, 1997;Saunders et al, 1993;Shibata et al, 1993;Bejarano and Valdivia, 1996;Spain et al, 1997;Sugiura et al, 1997). We recently identified titin as a chromosomal component using a human autoimmune scleroderma serum (Machado, 1998;Machado et al, 1998).…”
Section: Machado and Andrewmentioning
confidence: 99%
“…However, it was recently demonstrated that some proteins required for sister chromatid cohesion are localized specifically in the centromere region during metaphase I and anaphase I (Kerrebrock et al 1995;Moens and Spyropoulos 1995). Unfortunately, the sera from patients with CREST rarely recognize plant centromeres (Mole-Bajer et al 1990;Palevitz 1990;Houben et al 1995). Therefore, no biochemical comparisons have been reported between the mitotic and meiotic centromere proteins of higher plants.…”
Section: Introductionmentioning
confidence: 95%
“…Results indicated that a few of the sera recognized centromeric regions of plants, implying that at least a portion of the centromeric proteins is shared among plants and animals (Mole-Bajer et al 1990 ;Houben et al 1995) . In plants, the first centromeric protein that was confirmed to be localized to the centromere region was CENP-C homologs in maize .…”
Section: General Remarksmentioning
confidence: 97%